Case-Control Study of Occupational Acute Myeloid Leukemia in the Republic of Korea - Min Young Park; Hyoung-Ryoul Kim; Jun-Pyo Myong; Byung-Sik Cho; Hee-Je Kim; Mo-Yeol Kang (Elsevier, 2023)
Background: We conducted a case-control study to identify high-risk occupations and exposure to occupational hazards for acute myeloid leukemia (AML). Methods: When patients with AML admitted to the Department of Hematology in the study hospital for the first time are referred to the Department of Occupational and Environmental Medicine, data on occupation are collected by investigators to evaluate work-relatedness. Community-based controls were recruited through an online survey agency, and four controls per case were matched. Occupational information was estimated using structured questionnaires covering 27 specific occupations and 32 exposure agents. Conditional logistic regression analysis was performed by pairing cases and controls. Results: In the analysis of the risk of AML according to occupational classification, a significant association was found in paint manufacturing or painting work (OR = 2.22, 95% CI: 1.03-4.81) and aircrew (OR = 6.00, 95% CI: 1.00-35.91) in males, and in pesticide industry (OR = 6.89, 95% CI: 1.69-28.07) and cokes and steel industry (OR = 2.00, 95% CI: 1.18-22.06) in ≥60 years old. Moreover, the risk of AML increased significantly as the cumulative exposure to thinners increased. In the analyses stratified by sex and age, the association between pesticide exposure and AML was significant in males (OR = 3.28, 95% CI: 1.10-9.77) and in ≥60 years old (OR = 6.22, 95% CI: 1.48-26.08). Conclusion: This case-control study identified high-risk occupational groups in the Republic of Korea including paint manufacturers and painters, aircrew, and those who are occupationally exposed to pesticides or paint thinners.